2007
DOI: 10.2139/ssrn.891735
|View full text |Cite
|
Sign up to set email alerts
|

Driven to Distraction: Extraneous Events and Underreaction to Earnings News

Abstract: Psychological evidence indicates that it is hard to process multiple stimuli and perform multiple tasks at the same time. This paper tests the investor distraction hypothesis, which holds that the arrival of extraneous news causes trading and market prices to react sluggishly to relevant news about a firm. Our test focuses on the competition for investor attention between a firm's earnings announcements and the earnings announcements of other firms. We find that the immediate stock price and volume reaction to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

31
361
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(394 citation statements)
references
References 13 publications
31
361
1
1
Order By: Relevance
“…Lin and Tamvakis (2010) Akin to the phenomenon of post earnings announcement drift (Hirshleifer et al, 2009) the e ect of an EP decision on EUA prices may not end on the day of the decision itself, but may continue for a short period after. Therefore we select 11 days in keeping with the ratio of Lin and Tamvakis (2010).…”
Section: Lin and Tamvakismentioning
confidence: 99%
See 2 more Smart Citations
“…Lin and Tamvakis (2010) Akin to the phenomenon of post earnings announcement drift (Hirshleifer et al, 2009) the e ect of an EP decision on EUA prices may not end on the day of the decision itself, but may continue for a short period after. Therefore we select 11 days in keeping with the ratio of Lin and Tamvakis (2010).…”
Section: Lin and Tamvakismentioning
confidence: 99%
“…A possible explanation for the strong e ect of EP decisions on EUA prices during times of low media exposure can be found in the Investor Attention Hypothesis (Barber and Odean, 2008;Da et al, 2011;Hirshleifer et al 2009Hirshleifer et al , 2013Vozlyublennaia, 2014). In an equity context this proposes that since attention is a limited resource, investors will make decisions about rms to which their attention has rst been drawn, and that until their attention is drawn to a stock its price will only slowly re ect new information due to lack of trading interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research, for example, has shown evidence of inattention to nonsaliently displayed prices (Hossain and Morgan 2006, Lee and Malmendier 2010, Simonsohn and Ariely 2008, to information that competes with attention grabbing or abundant information (DellaVigna and Pollet 2009, Eisensee and Strömberg 2007, Hirshleifer et al 2009), and to future events occurring beyond immediate planning horizons (Che et al 2007, DellaVigna andPollet 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Long-term store contains learned sequences of information processing that may be initiated by a control process or by environmental or internal information input but that are then executed automatically with few demands upon the capacity of short-term store [21][22][23][24][25][26][27][28][29][30]. This automatic process can be activated in response to a particular input configuration, where the inputs may be externally or internally generated and include the general situational context, or it will be activated automatically without the necessity of active control or attention by the subject [31][32][33][34][35][36].…”
mentioning
confidence: 99%